Kinetic modeling of hydrogenolysis of glycerol to 1,2-propanediol using a chromium-free Ni–Cu–SiO2 nanocomposite catalyst - Woo, Yesol; Lee, Maeum; Cha, Seung Hyeok; Hwang, Dong Won; Park, Myung June (Reaction Kinetics, Mechanisms and Catalysis, 2023)
Kinetic modeling of the hydrogenolysis of glycerol was performed; a chromium-free Ni–Cu–SiO2 nanocomposite catalyst was used to produce 1,2-propanediol (1,2-PDO) at a low hydrogen-to-glycerol ratio. Kinetic data were produced in a fixed-bed reactor under a variety of temperatures, hydrogen-to-glycerol ratios, and space velocities. The reaction rates were developed based on the two-step reaction mechanism (the production of 1,2-PDO via acetol) and the reaction pathways for the byproducts observed in the experimental study. The kinetic parameters were estimated by fitting kinetic data, and the validity of the developed model was corroborated. Further analysis using the model showed that the reaction at a high temperature and a low space velocity could accomplish 95% conversion of glycerol; However, the low temperature was preferred to minimize the production of unwanted species (intermediate and byproducts) at the slight expense of conversion.
Keywords: 1,2-propanediol; Chromium-free; Fixed bed reactor; Fixed-bed reactors; Kinetic data; Kinetic models; Nanocomposite catalyst; Parameters estimation; Propanediols; Space-velocity; 1,2-propanediol; Glycerol; Hydrogenolysis; Kinetic modeling; Parameter estimation